Evaluation of early oral cavity cancer treatment quality at a single institution. (8th November 2018) - Chang, Steven; Sanii, Ryan; Chaudhary, Hamad; Lewis, Carol; Seidman, Michael; Yaremchuk, Kathleen
Abstract : Objective: To evaluate the adherence to oral cavity quality guidelines endorsed by the American Head and Neck Society (AHNS) at a large tertiary care hospital. Methods: This retrospective study identified patients treated for early‐stage oral tongue squamous cell carcinoma at a tertiary care hospital from 1992 to 2013. Patient charts were reviewed for 26 process quality measures and four key indicator process quality measures as endorsed by the AHNS. Patients were then grouped by diagnosis date either before (historical group, 1992–2007) or after (current treatment group, 2008–2013) the published process quality measures from the AHNS. Descriptive statistics were used to evaluate the rates of adherence for each process quality measure within the 2 groups. Results: Of the 57 patients identified, 29 were female (51%). The mean age was 62.3 years. A majority of the oral cavity cancers were stage I (59.6%), followed by stage II (35.1%) and stage III (5.3%). Compliance with the process quality measures was in the acceptable range in both cohorts. However, several areas demonstrated lower adherence in both cohorts. Statistically significant improvements were noted between the two cohorts, which showed a measurable improvement in adherence to process quality measures in several key areas over time. Conclusion: Using the process quality measures proposed by the AHNS, adherence to the process quality measures for early‐stage oral cavity cancer care at a tertiary care center was successfully evaluated. In general, good compliance with the proposed process quality measures was found and several areas for improvement were identified. Level of Evidence: 2c Laryngoscope, 129:1816–1821, 2019